2014
DOI: 10.1021/ol503008t
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Synthesis of 3-Halo-5-Substituted Isoxazoles from 1-Copper(I) Alkynes and Dihaloformaldoximes

Abstract: A tandem synthesis of 3-halo-5-substituted isoxazoles has been developed from 1-copper(I) alkynes and dihaloformaldoximes under base-free conditions. Thus, 1,3-dipolar cycloaddition and all its drawbacks can now be avoided completely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…More recently, Wang and Hu proposed copper(I)‐catalyzed cycloisomerization as a part of the mechanism in the synthesis of 3‐halo‐5‐substituted isoxazoles from copper acetylides and dihaloformaldoximes (not shown) 80…”
Section: Synthesis Of Isoxazoles Via Cycloisomerization Reactionsmentioning
confidence: 99%
“…More recently, Wang and Hu proposed copper(I)‐catalyzed cycloisomerization as a part of the mechanism in the synthesis of 3‐halo‐5‐substituted isoxazoles from copper acetylides and dihaloformaldoximes (not shown) 80…”
Section: Synthesis Of Isoxazoles Via Cycloisomerization Reactionsmentioning
confidence: 99%
“…As shown in Scheme , Fokin reported that the 1,3‐dipolar cycloaddition between a terminal alkyne 5 a and a nitrile oxide (in situ generated from α‐chloro‐oxime 49 ) can be improved significantly under CuAAC conditions. Unfortunately, no improvement was observed when dibromoformaldoximes 50 were used as substrates, because the bromonitrile oxide was generated too fast to be controlled in the presence of a base.…”
Section: Premade 1‐copper(i) Alkynes In Cycloadditionsmentioning
confidence: 99%
“…To avoid generating the hydrido-palladium species, we investigated an alternative Sonagashira coupling procedure. 16 In this protocol, Pd(PPh 3 ) 4 was used as catalyst, pre-synthesized copper(I) phenylethyne 17 as reactant, and…”
Section: Letter Syn Lettmentioning
confidence: 99%